Analisis nilai tambah usaha penangkapan Kepiting Bakau di Desa Eelahaji Kecamatan Kulisusu Kabupaten Buton Utara - Adrianto, Yogi; Rosmawati; La Onu, La Ola; Riani, Irdam; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aims to examine the fisherman's profits from the sale of mud crabs and to examine the added value of the sale of mud crabs in Eelahaji Village, Kulisusu District, North Buton Regency. This research was conducted in March 2022. The sampling technique in this study used the census method. Data collection consists of primary data and secondary data, the data analysis used in this research is profit analysis and value added analysis. The results of the research show that the total profit obtained by 8 fisherman catching mud crabs is Rp. 19,652,062/month and the added value is of selling mud crab Rp. 29,537,000.